HOW SUITABLE ARE NDO-LID AND PGL-I IN RAPID DIAGNOSTIC TESTS FOR SCREENING OF LEPROSY? A REVIEW OF DIAGNOSTIC STUDIES - Gabriela Valencia Putri Husodho; Anatalya Diah Ayu Kumalasari; Agyta Hanifa Faiza (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Indonesia has the third highest prevalence of leprosy, a neglected tropical disease caused by the “Mycobacterium leprae complex which causes neuropathy and hypopigmented skin lesions with hypoesthesia. The main problem in eradicating leprosy is due to its negative social stigma and prevalence in lower socioeconomic populations, as the gold standard for leprosy diagnosis is histopathology of skin smears. Hence, cost and time effective screening tools are needed. PGL-I and NDO-LID are antigens that have been developed as biomarkers used in serological assays, one of them being rapid lateral flow tests. Therefore, a rapid test utilizing a combination of PGL-I and NDO-LID as its marker is potentially a suitable tool for leprosy screening in areas with limited access to healthcare. Objective: To evaluate the diagnostic potential of PGL-I and NDO-LID in rapid lateral flow tests for leprosy. Methods: This literature review was done by using the search engines PubMed, Science Direct, and SpringerLink.  Results: Diagnostic potential studies for PGL-I rapid tests using UCP-LFA and Gold-LFA showed high overall sensitivity and specificity for leprosy patients, with more positive results in MB and PB patients. NDO-LID rapid test diagnostic studies which used the also showed similar results. However, these tests are not as accurate as ELISA and histopathology, but modifications such as additional biomarkers can be used to improve its utility. Conclusion: PGL-I and NDO-LID have good sensitivity and specificity from the results of various diagnostic studies, thus are potentially suitable for field screening of leprosy.